Metabolite concentrations and the expression profiles of the corresponding metabolic pathway genes in eggplant (Solanum melongena L.) fruits of contrasting colors - M. A. Filyushin; E. A. Dzhos; A. V. Shchennikova; E. Z. Kochieva (Вавиловский журнал генетики и селекции)
Eggplant (Solanum melongena L.) ranks fifth in importance among vegetable crops of the Solanaceae family, in part due to the high antioxidant properties and polyphenol content of the fruit. Along with the popular purplefruited varieties of S. melongena, there are cultivars, the fruits of which are rich in phenolic compounds, but are whitecolored due to the lack of anthocyanin biosynthesis. Determination of the amount of anthocyanins and other phenolic compounds, as well as carotenoids and sugars, is included in the assessment of the quality of eggplant fruits of commercial (technical) ripeness. In addition to antioxidant and taste properties, these metabolites are associated with fruit resistance to various stress factors. In this study, a comparative analysis of the content of anthocyanins, carotenoids and soluble sugars (sucrose, glucose, fructose) in the peel and pulp of the fruit of both technical and biological ripeness was carried out in purple-fruited (cv. Vlas) and white-fruited (cv. Snezhny) eggplant accessions of domestic selection. The peel and pulp of biologically ripe fruits of the cvs Vlas and Snezhny were used for comparative transcriptomic analysis. The key genes of the flavonoid and carotenoid metabolism, sucrose hydrolysis, and soluble sugar transport were shown to be differentially expressed between fruit tissues, both within each cultivar and between them. It has been confirmed that the purple color of the peel of the cv. Vlas fruit is due to substantial amounts of anthocyanins. Flavonoid biosynthesis genes showed a significantly lower expression level in the ripe fruit of the cv. Vlas in comparison with the cv. Snezhny. However, in both cultivars, transcripts of anthocyanin biosynthesis genes (DFR, ANS, UFGT) were not detected. Additionally, the purple fruit of the cv. Vlas accumulated more carotenoids and sucrose and less glucose and fructose than the white fruit of the cv. Snezhny. Biochemical data corresponded to the differential expression pattern of the key genes encoding the structural proteins of metabolism and transport of the compounds analyzed.